Feasibility of using seismic reflection surveys to discover iron oxide copper gold deposits in the Gawler Craton, South Australia - Okan, Evans; Kepic, Anton; Williams, Peter (Earthdoc, 2013)
IOCG deposits remain important sources of copper and gold in Australia especially since the discovery of the giant Olympic Dam deposits in 1975. They are considered to be metasomatic expressions of large crustal-scale alteration events driven by intrusive activity and are associated with felsic igneous rocks in most cases, commonly potassic igneous magmatism, with the deposits being commonly ~2.2 –1.5 Ga in age (Harrison, 2009). They tend to be enriched in Ca, Fe, Mn and P, with many deposits exhibiting an additional distinctive enrichment in Fe with economic levels of Cu, Au, Ag, Rare Earth Elements (REE), and U (Esdale, et al 1994). Such deposits have large net tonnages of economic minerals. Due to these distinguishing features, the IOCG class of deposits is a prime target for exploration by the mining industry. Although IOCG’s are largely classified by their geochemical characteristics many have significant petrophysical contrasts in magnetic susceptibility and/or density. Thus, potential field geophysical methods are typically used to detect both the major structures that lead to the location of prospective targets and the deposits themselves. Such methods have poor resolution at depth, and are limited to either directly detecting shallow targets or very large deposits with sufficient contrast in areas with significant cover, such as the Gawler Craton. Thus, the traditional approaches to exploration for IOCG deposits in the Gawler Craton are becoming less effective and more expensive; hence another method such as seismic reflection is proposed.